Understanding content dissemination on sensemaking: WHO’s social listening strategy on X during the initial phase of COVID-19 - Kumble Sushma; Diddi Pratiti; Bien-Aimé Steve (Online Media and Global Communication)
Guided by the Crisis and Emergency Risk Communication model (CERC, Reynolds and Seeger 2005. Crisis and emergency risk communication as an integrative model. Journal of Health Communication 10(1). 43–55.), the present study aimed to study how X (formerly Twitter) users sensemaking and efficacy based message. Additionally, the study also aimed to understand how the World Health Organization (WHO) responded to the emerging conversation.